PULMONARY ARTERIOVENOUS MALFORMATION: A RARE CAUSE OF CYANOSIS IN A CHILD - Krstevska Blazhevska, Svetlana; Chadikovski, Vladimir; Conevska, Biljana (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Pulmonary arteriovenous malformations are rare, abnormal low resistance vascular structures that connect a pulmonary artery to a pulmonary vein, thereby bypassing the normal pulmonary capillary bed and resulting in an intrapulmonary right-to-left shunt. We report a 11 -year - old boy who presented with fatigue, cyanosis since the age of 10. Computed tomography pulmonary angiogram showed a large pulmonary arteriovenous malformation (PAVMs) at the left and right lung. Most of the multiple arteriovenous malformations were occluded with Amplatzer vascular plug. He is now still cyanotic, with blood oxygen saturation of 88%. Keywords: arteriovenous malformation, cyanosis, pulmonary arteriovenous malformation, pulmonary vascular anomaly.